y = x^2 -4x
x = -1
y = (-1)^2 - 4×-1=1+4 = 5
x= 0
y = (0)^2 - 4×0 = 0
x = 1
y = 1^2 -4×1 = 1-4 = -3
x = 2
y = 2^2 -4×2 = 4-8 = -4
x=3
y = 3^2 - 4×3 = 9-12 = -3
x = 4
y = 4^2 - 4×4 = 16 - 16 = 0
now 2nd equation
y = 2x^2 + x
x = -2
y = 2 (-2)^2 + (-2)= 8-2 = 6
x = -1
y = 2 (-1)^2+(-1)= 2-1 = 1
x = 0
y = 2(0)^2 +0 = 0
x = 1
y = 2 (1)^2 + 1 = 3
x = 2
y = 2(2)^2+2= 8 + 2 = 10
We can use completing the square.We add 16 and subtract 7 to both sides. Now we get m^2+8m+16=9. The left sides becomes (m+4)^2=9. Taking the square root of both sides and subtracting 4 we get -1 and -7.
Y = a (x + 3)² - 1
Let's take the point (-1;3)
3 = a ( -1 + 3)² - 1
3 = 4a - 1
4a = 4
Therefore a = 4/4 = 1
(x+3)² - 1
= x² + 6x + 9 - 1
= x² + 6x + 8
The answer would be y = x² + 6x + 8.
Hope this helps !
Photon
<span>36 ÷ 3^2 +4*2-1
</span>=36 ÷ 9 + 4*2-1<span>
=</span>4 + 8 - 1
= 11
USING PEMDAS
The anwser is for the question tht u are looking for is no other then the first anwser A!!!